Solar SkyHaul hybrid drone - Masri, Airin Najiha; Fadzly Helmy, Farra Halissa; Raszali, Nabila Batrisyia; Hamzah, Nur Jasmine; Ariffin, Nurul Azrin (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Currently, the use of drones helps industries extensively, offering faster operations, improved efficiency, and access to hard-to-reach areas. The Solar SkyHaul, a hybrid solar-powered drone, is one of our products that was created to overcome the problems of traditional drones, including their short battery life, small payloads of capacity, and susceptibility to environmental factors. The drone's integration of lithium-Sulphur batteries and high-efficiency solar panels greatly increases flying time and lowers carbon emissions, both of which are in accordance with international sustainability objectives. Its objective is to provide more dependable and adaptable UAV solutions for delivery, surveillance, agriculture, and emergency response applications. A cargo capacity of up to 15 kg, adaptive mission planning, and real-time environmental sensors for danger identification are among its novel characteristics, which make it appropriate for crucial logistics in remote or disaster-affected locations. According to our survey of 31 respondents, there is considerable support (87.1%) for the use of drones for parcel delivery. Users acknowledge the efficiency and environmental benefits of this technology, although some are concerned about security and weather effects. The potential for commercialization of drones is significant, especially in the courier, medical, and humanitarian sectors where quick, self-sufficient delivery is crucial. By facilitating operations in areas with inadequate infrastructure and reducing operating expenses, Solar SkyHaul has the potential to revolutionize logistics and promote sustainable development objectives. As to conclude, this invention offers a forward-thinking solution for robust, environmentally friendly aerial transport systems by fusing renewable energy, intelligent automation, and sophisticated design.